2021
DOI: 10.9734/jpri/2021/v33i28a31519
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Epitope Prediction of Birch Betv 1 and Hazel Cor A1 Towards B-Cells

Abstract: Background: White birch and hazel allergens, namely Bet v1 and Cor a1 are known allergens, but their allergen specificity is not yet characterized. Objective: To map the antigenic determinants responsible for IgE binding utilizing in silico modelling and docking of the peptides against IgE antibody. Methods: The antigen sequences were cut into peptides are docked against the IgE antibody and those with the highest docking scores are further studied for the bond interactions. The overlapping sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Proteins unstable to digestive enzymes are still considered responsible for triggering severe allergic reactions. Several major food allergens, such as milk Bos d 8, egg Gal d 1, shrimp Pen a 1, apple Mal d 1, hazelnut Cor a 1.04, and celery Api g 1, were quite labile during digestion (Boddakayala et al., 2021; Souza, 2020). In fact, there are potent allergens that do not share the commonly attributed physicochemical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Proteins unstable to digestive enzymes are still considered responsible for triggering severe allergic reactions. Several major food allergens, such as milk Bos d 8, egg Gal d 1, shrimp Pen a 1, apple Mal d 1, hazelnut Cor a 1.04, and celery Api g 1, were quite labile during digestion (Boddakayala et al., 2021; Souza, 2020). In fact, there are potent allergens that do not share the commonly attributed physicochemical properties.…”
Section: Introductionmentioning
confidence: 99%
“…The allergen generally exhibits crossreactivity among hazelnut and birch or also alder and hornbeam. 6 Cor a 1 is the major hazel allergen and displays a significant level of homology towards the Bet v 1, major birch allergen which highlights the cross-reactivity. 7 Cor a 1 is a heat-sensitive protein found in both hazel and hazelnut 8 whose involvement impacts the detection of hazelnut allergy.…”
Section: Hazelmentioning
confidence: 97%
“…It is thought that the more food allergens maintain their structural integrity in the process of gastrointestinal digestion, the more they retain their own allergenicity . However, this is not always true, and recent studies have confirmed that many food allergens are unstable during gastrointestinal digestion. , During this process, their spatial structures are likely to be changed due to the hydrolysis of digestive enzymes, including loosening, unfolding, reaggregation, etc. , which affect the shape of allergens presented to the immune system, and thus affect the allergenic potential. , The structural changes of TM in Antarctic krill before and after gastrointestinal digestion in vitro were measured and analyzed in order to further explore the effect of gastrointestinal digestion on its allergenicity.…”
Section: Introductionmentioning
confidence: 99%